A scalable, efficient, and safe method to prepare high quality DNA from mycobacteria and other challenging cells. (May 2020) - Epperson, L. Elaine; Strong, Michael
Abstract: The rapid development in sequencing technology is creating an increase in demand for largely intact DNA as starting material as very long strands of DNA are sequenced directly to generate reads that are thousands of bases long. Organisms with thick cell walls are difficult to lyse, often impacting both DNA recovery and quality. Consequently, most mycobacterial DNA extraction methods require bead-beating steps or toxic chemicals. Here we present an updated method that yields abundant, high quality genomic DNA from M. tuberculosis and diverse nontuberculous mycobacterial (NTM) species, in addition to complex biological communities from a variety of sources. This method eliminates the time-consuming phenol and chloroform extraction and ethanol precipitation steps, and high quality DNA from up to 96 samples can be extracted in about 2–3 h of hands-on time. This DNA is suitable for long and short read sequencing technologies as well as PCR and qPCR amplification.